Early initiation of thromboembolic prophylaxis in critically ill trauma patients with high-grade blunt liver and splenic lacerations is not associated with increased rates of failure of non-operative management. (January 2023) - Moore, Kerry; Barton, Cassie A; Wang, Yuxuan; Ran, Ran; Chi, Albert; Rowell, Susan; Schreiber, Martin
Background: Non-operative management (NOM) is the current standard of care of hemodynamically stable patients with traumatic blunt solid abdominal organ injuries. Guidelines do not define the optimal timing of initiation of venous thromboembolism (VTE) prophylaxis in this population, and fear of failure of NOM may lead to delayed initiation of prophylaxis specifically in patients with high-grade injuries. Methods: This was a single-center, retrospective study of patients with high-grade (AAST grades ≥3) blunt liver and splenic lacerations presenting to our level 1 trauma center between January 2010 and October 2017. Patients were divided into groups based on timing of low-molecular weight heparin (LMWH) initiation for VTE prophylaxis. The primary outcome was rate of failure of NOM, defined as the need for interventional radiology or surgical intervention for management of abdominal organ bleeding. Secondary outcomes included rates of VTE, lengths of ICU and hospital stay, and in-hospital mortality. Results: A total of 207 patients with high-grade blunt liver and splenic injuries undergoing an initial attempt at NOM were identified. The distribution of grades 3, 4, and 5 liver and splenic injuries were similar across all groups. Overall, 55.5% of patients received LMWH during their index admission. Early administration of LMWH was not associated with a statistically significant increased risk of failure of NOM ( p = 0.054). Rates of VTE and in-hospital mortality were similar. Conclusions: Early initiation of VTE prophylaxis was not associated with an increased rate of failure of NOM in patients with high-grade blunt abdominal organ injuries in patients who survived 24 h post-admission and did not require massive transfusion; however, the study was likely underpowered to detect a difference among groups due to small sample size.